BRIDGING TRADITIONS: THE SYNERGY OF INDIGENOUS CUSTOMS AND ISLAMIC PRINCIPLES IN SUSTAINABLE NATURAL RESOURCE MANAGEMENT - Dedisyah Putra; Martua Nasution (QANUN: Journal of Islamic Laws and Studies, 2026)
This study explores the dynamic relationship between indigenous customs and Islamic principles in promoting sustainable natural resource management. Grounded in a socio legal and normative approach, the research examines how local wisdom embedded in customary practices can be harmonized with Islamic ethical and legal frameworks to address contemporary environmental challenges. Indigenous communities have long upheld ecological balance through traditions that regulate resource use, conservation, and communal responsibility. Similarly, Islamic teachings emphasize stewardship (khilāfah), balance (mīzān), and the prohibition of environmental destruction (fasād), offering a moral and theological foundation for sustainability. Through qualitative analysis of relevant literature and selected case studies, this research identifies areas of convergence between customary norms and Islamic values, particularly in forest management, water conservation, and land use. The findings reveal that the integration of these two systems not only strengthens environmental governance at the local level but also enhances community participation and compliance. Moreover, the synergy between adat and Sharia based principles provides a culturally resonant and spiritually grounded model for sustainable development. The study concludes that bridging indigenous traditions with Islamic principles offers a holistic and context sensitive framework for natural resource management. This approach is especially relevant in plural legal systems such as Indonesia, where the recognition of customary law alongside religious and national legal systems can contribute to more inclusive and sustainable environmental policies.